Biochar in the circular bionutrient economy - Johannes Lehmann; Edmundo Barrios; Mariana Devault; Lucinda Li; Rebecca Nelson; Johan Six; John Trimmer (Proceedings of the National Academy of Sciences, 2025)
The circular bionutrient economy is defined here as the circular economy of nutrients in managed organic residues. Here, we posit that biochar technology can stimulate the circular bionutrient economy by meeting the following three requirements: 1) nutrients are captured in a dry form, increasing market value and lowering transportation cost; 2) individual nutrients can be captured separately and combined as needed for particular plants and soils; 3) all pathogens and most pollutants can be removed with the notable exception of heavy metals. Pyrolysis and associated moisture removal enabled by the energy released during pyrolysis decreases weight of solid excreta by 85 to 90% and volume by 74 to 90%. This will lower storage and transport costs allowing redistribution of nutrients from production to processing and consumption of food. Incorporating liquid organic residues into nutrient recovery processes is crucial to the circular bionutrient economy. For example, N fertilizer from human feces would only generate about 2% (2.0 to 2.4 Tg N y −1 ) of current global N application, whereas including urine could increase this fraction to 16 to 17% (15.7 to 16.9 Tg N y −1 ). Nutrient acquisition by plants can be increased by biochar through nutrient retention and pH buffering in soil. We posit that leveraging biochar to close the nutrient circle requires public–private partnerships in forms of a community of practice and green alliances. These must develop a marketable product that incentivizes private investment. Such products may only be cost competitive with established fertilizer products by internalizing external environmental costs possibly through market mechanisms including but not limited to carbon credits.